Bioversity International Annual Report 2011: Sustainable agriculture for food and nutrition security - Bioversity International (Bioversity International, 2012)
Throughout this 2011 Annual Report, you will find examples of Bioversity International’s work with partners and stakeholders from Africa to Asia to the Americas. You will also find information about our Board of Trustees, supporters and finances. It also includes a list of our 2011 scientific publications.